Telaah Pustaka: Heterocyclic Aromatic Amines (HAA), Karsinogen Pemicu Kanker dalam Olahan Daging Panggang / Bakar / Goreng - Eko Saputro (Jurnal Kewidyaiswaraan, 2020)
People are very fond of consuming satay, grilled ribs, grilled/fried chicken/duck because it is very delicious but consumers still do not understand that there are carcinogenic consequences of heterocyclic aromatic mines (HAA) which are harmful to health. This paper aims to explore HAA and various ways that have succeeded in minimizing HAAs levels so that consumers can still enjoy these foods safely and comfortably. This paper was compiled based on a systematic literature review, the authors conducted a content analysis on 41 peer-reviewed journal articles. Thermal meat processing is an important process to ensure microbiological safety, eliminate antinutrical factors, improving digestibility and bioavailability of nutrients and develop the profile of the color, aroma and flavor attributes that we want. However, this process also turns out to bring about carcinogens (cancer triggers), HAA and others by-product that are potentially harmful to our health in the long run. Their formation is highly dependent on various factors such as cooking method, cooking time, cooking temperature, type of meat, fat contents, moisture contents, pH and creatinine contents of meat. Many studies conclude that these HAAs are responsible for causing cancers in humans and animals. The results of this literature review provide practical information that can be applied by producers or housewives to minimize HAAs levels in finished products, which is choosing the right sugar for marination; addition of synthetic antioxidants; addition of natural antioxidants; addition of phytochemical and herbal extracts; and pretreatment using a microwave.